2016
DOI: 10.1590/0104-0707201600003680013
|View full text |Cite
|
Sign up to set email alerts
|

Modelo De Assistência Pré-Natal No Extremo Sul Do País

Abstract: Este estudo se propôs a conhecer o modelo de atenção à saúde utilizado na assistência pré-natal em unidades de Estratégia de Saúde da Família. Apresenta abordagem qualitativa e exploratória e foi realizado em três unidades de Estratégia Saúde da Família de um município do sul do Brasil. A coleta de dados foi desenvolvida por meio de entrevista individual com 10 gestantes que se encontravam no terceiro trimestre gestacional e os resultados obtidos foram submetidos à análise temática. A partir dos dados, foram e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 15 publications
0
3
0
14
Order By: Relevance
“…Thus, addressing pregnant women on prenatal consultations, a study showed that they were restricted to prenatal care, such as performing physical examination and requesting laboratory tests, but not highlighting educational aspects, especially when relating to the signs alert and labor. 5 In contrast to the data presented, a study on health education during pregnancy indicated that 56.4% reported they had received guidance on the signs of labor by health professionals, and the nurse was the most cited professional 6 in being the educator.…”
Section: Discussionmentioning
confidence: 72%
“…Thus, addressing pregnant women on prenatal consultations, a study showed that they were restricted to prenatal care, such as performing physical examination and requesting laboratory tests, but not highlighting educational aspects, especially when relating to the signs alert and labor. 5 In contrast to the data presented, a study on health education during pregnancy indicated that 56.4% reported they had received guidance on the signs of labor by health professionals, and the nurse was the most cited professional 6 in being the educator.…”
Section: Discussionmentioning
confidence: 72%
“…In addition, the influence of the biomedical model on the accomplishment of prenatal tests was emphasized, with emphasis on anthropometric data recording, obstetrical physical examination, on the request and/or evaluation of exams and prescription of medications. The influence of the biomedical model on prenatal care was also one of the research findings on prenatal care in Family Health Strategy units of a municipality in the south of Brazil (18) . Thus, the importance of developing strategies for a professional practice based on an expanded vision of the health-disease process, with the definition of careflows that foster interdisciplinarity, comprehensiveness and humanization as care management tools.…”
Section: Management Of Prenatal Nursing Care At a Health Center In Anmentioning
confidence: 98%
“…Observou-se a atitude de confiança, ao descreverem que o tempo de atuação profissional contribui para estreitar o elo de confiança e fortalecer o vínculo com os clientes, famílias e comunidade. Estudos relatam que a equipe da ESF deve privilegiar o estabelecimento das relações de vínculo com a comunidade, facilitando a aproximação do profissional com o usuário e o conhecimento de sua área 4,18 . A gestação é um momento de muitas transformações para mulher, com isso, necessita ser acompanhada por profissionais que compreendam seus sentimentos, tornando esse momento a oportunidade de construção de vínculos 5 .…”
Section: Como a áRea é Pequena E Já Tem 3 Anos Que Estou Trabalhando unclassified